CHALLENGES OF USING TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION LEARNING (Application of Flipped-Classroom in Class X PAI Subjects at SMA Plus Pagelaran Subang) - Fitri Meliani; Dandy Sobron Muhyiddin; Uus Ruswandi; Bambang Samsul Arifin; Suzana Suzana (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
PAI material at various levels of high school has different characteristics compared to the levels below, namely in terms of content, weight, and deepening of the material both psychologically, philosophically, sociologically, and technologically. This article aims to discuss the use of flipped-classroom in PAI subjects at the high school level, to find out its implementation, disadvantages, advantages, and ethical issues that arise. The method used is qualitative with a descriptive approach. The data collected is from interviews with PAI class X teachers, based on interviews, it can be concluded that by using a flipped classroom, the advantage for PAI teachers is to become more skilled in the use of technology. Students are more independent and activate their time to study. But in the lack of flipped-classroom, teachers have become busier in preparing materials in the form of videos or oPPTsPT so that students can access them at home. As for students, their free time has become less. The challenge that arises is that PAI learning has long used the teacher center so that students can learn as well as get suri tauladan directly from the teacher's knowledge. Meanwhile, with flipped classrooms that use student center methods and technology, there are fewer opportunities for students to get knowledge transfer, value transfer, and character building from suri tauladan PAI teachers.